A comparative study on the efficacy of four anthelmintics on some important reindeer parasites - Magnus Nordkvist; Claes Rehbinder; D. Christensson; C. Rönnbäck (Rangifer, 1983)
Four anthelmintic preparations were tested against some of the most important parasites of reindeer, i.e. warble fly (Oedemagena tarandi), nostril fly (Cephenemyia trompe), brainworm (Elaphostrongylus rangiferi), and lungworm (Dictyocaulus viviparus). Their efficacy against intestinal nematodes was also registered. Test drugs were Fenthion (Bayer), Fenbendazole (Hoechst), Mebendazole (Janssen), and Ivermectin (Merk Sharp & Dohme). Against O. tarandi and C. trompe Ivermectin was 100% effective and Fenthion 86 and 100% respectively. The efficacy of Fen- and Mebendazole against these parasites was not significant. Against E. rangiferi the benzimidazole compounds were highly effective, with Mebendazole a bit ahead. Ivermectin had a moderate effect and Fenthion had no effect on this parasite. Against D. viviparus Fenbendazole, Mebendazole and Ivermectin were of equal, moderate-high effectiveness. No drug had a complete effect on the «arrested» larvae of D. viviparus. Fenthion had no effect at all. Fenbendazole and Ivermectin were both 100% effective against intestinal nematodes. Mebendazole was less effective and Fenthion had no effects. Ivermectin is considered to be the overall most effective anthelmintic in this test. En jamforande studie av effekten av fyra anthelmintika mot några betydelsesfulla parasiter hos ren. Abstract in Swedish / Sammandrag: Fyra antiparasitmedel har prôvats mot några av renens viktigaste parasiter, nàmligen hudkorm (Oedemagena tarandi), svalgkorm (Cephenemyia trompe), hjårnmask (Elaphostrongylus rangiferi) och lungmask (Dictyocaulus viviparus). Vidare har medlens effekt på mag- tarmnematoder (Trichostongylider) också noterats. De prôvade medicinerna var Fenthion (Bayer), Mebendazole (Leo/Janssen), Fenbendazole (Hoechst) och Ivermectin (Merck Sharp & Dohme). Mot hud- och svalgkorm var Ivermectin 100% effektivt medan for Fenthion effekten var 86 resp 100%. Effekten av Fen- och Mebendazole mot de båda parasiterna var inte signifikant. Mot hjårnmask noterades mycket hôg effekt av ...